Notice of meeting - Phillips, Morgan, 1902-
C03-0010-001 Telegraphic Address: "LABREPCOM, SOWEST, LONDON." Telephone: VICTORIA 8016, 8017, 8018, 8019 THE LABOUR PARTY TRANSPORT HOUSE (South Block), SMITH SQUARE, LONDON, S.W.1 Hon. Treasurer: GEORGE LATHAN, M.P. Secretary: J.S. MIDDLETON National Agent: GEORGE R. SHEPHERD MP/LMG November 5th, 1937. Dr. H.B. Morgan, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Colleague, Labour's Spain Campaign Albert Hall Demonstration Sub-Committee. A meeting of the above Sub-Committee will be held in the House of Commons on Monday next, November 8th, at 4 p.m. in a Committee Room booked in the name of Miss Ellen Wilkinson, M.P. It is important that every member of the Committee should make a special effort to attend. Yours sincerely, Morgan W. Phillips Propaganda Officer. Read the "DAILY HERALD" every day and " LABOUR" and "THE LABOUR WOMAN" every month 292C/946/3/10